"Detección y corrección de inconsistencias en esquemas lógicos de base de datos" - Pin Zamora, Angélica Claribel (2016)
The present research project proposes a proposal of a tool for the detection and correction of inconsistencies in logical database schemas. In which it developed through the analysis of each of the existing methods for the detection of inconsistent cardinality restrictions in the conceptual schema of a database, where it managed to determine one of the inconsistencies that can occur and correct through the implementation of the algorithm called "inconsistency of cyclical reference", reason why is considered possible the realization of this new proposal. Once determined the type of inconsistency to solve with the implementation of the algorithm we proceeded to search the computational complexity where determined to n as the number of nodes, m the number of edges, and c the amount of cycle. The algorithm of detecting and correcting logical inconsistencies of database was implemented in an ERECASE tool, which allowed testing to validate the proper operation of the algorithm. Keywords: inconsistencies, constraints of cardinality, computational complexity